Sewing success? : employment, wages and poverty following the end of the multi-fibre arrangement - Gladys Lopez Acevedo; Raymond Robertson; World Bank (Directions in development (Washington, D.C.)., Poverty., 2012)
The end of the MFA was followed by rising apparel exports, falling prices, and a reallocation of production and employment between countries. There were also significant changes within countries. The first main finding of this report is that export and employment patterns after the MFA/ATC did not necessarily match predictions. While many predicted that production would shift to low-wage countries, this book shows Read more...